Guarding Gonadal Health: Ascorbic Acid Attenuates Methylphenidate-Induced Toxicity in Rats (Journal of Fatima Jinnah Medical University, 2026)
Background: Methylphenidate (MPH), a prevalent treatment for Attention Deficit Hyperactivity Disorder (ADHD), offers therapeutic benefits but raises concerns about its impact on testicular health, potentially leading to reproductive complications. Ascorbic acid (Vitamin C) is a potent antioxidant renowned for its capacity to combat oxidative stress and enhance cellular resilience. This study aimed to evaluate the effects of ascorbic acid on methylphenidate-induced testicular toxicity in Albino rats by assessing histopathological changes in the testes.Methods: Thirty Albino male rats were randomly assigned to three groups, each containing ten rats. The control group (Group A) received normal saline for 50 days. The two experimental groups received treatments as follows: Group B received 2 mg of MPH orally for 50 days, and Group C received 2 mg of MPH orally for 50 days, followed by 50 mg of Ascorbic acid orally for an additional 10 days. Testicular histopathology was performed 60 days after the procedure.Results: Histological analysis revealed a significant reduction in germinal epithelium height in the MPH group (57.52 ± 5.59 µm) compared with controls (175.76 ± 5.21 µm). There was a partial recovery when treated with ascorbic acid (107.22 ± 8.47 µm). Similarly, the seminiferous tubule diameter was decreased in the MPH group (295.64 ± 36.31 µm) as compared to controls (370.71 ± 4.87 µm), which was increased after ascorbic acid treatment (401.83 ± 11.87 µm). Interstitial space thickness significantly increased after MPH exposure (46.46 ± 6.19 µm) relative to controls (8.08 ± 4.25 µm), which was reduced after ascorbic acid treatment (14.94 ± 3.71 µm). Conclusion: These findings suggest that ascorbic acid may effectively mitigate testicular toxicity associated with methylphenidate, preserving spermatogenesis and supporting overall reproductive health.
Keywords: Methylphenidate; Ascorbic Acid; Testicular Diseases; Oxidative Stress; Antioxidants; Attention Deficit Hyperactivity Disorder